A PRACTICAL GUIDE TO UNDERTAKING SCOPING REVIEWS FOR PHARMACY CLINICIANS, RESEARCHERS, AND POLICYMAKERS - Fahda Dakheel Baker Al enazi, Hanan Saleh Almasmary, Sara Basheer Shelash AlEnzy, Eman Mohammad Omar Alshammari, Safiyah Mohammad Saeed Alghamdi, Maha Abdulrahman Ibrahim alowais, Mashail Kaid Aloudah, Amal muhammad alasmari (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Scoping reviews are a valuable evidence synthesis methodology. They can be used to map the evidence related to any topic to allow examination of practice, methods, policy, and where (and how) future research could be undertaken. As such, they are a useful form of evidence synthesis for pharmacy clinicians, researchers and policy makers to review a broad range of evidence sources.